ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PADA MEBEL FAMILY BERAU - SITI MUNAWAROH (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2021)
The purpose of this study is to study whether the cost of goods is in accordance with the method of pricing work orders. Because using the order costing job can determine the cost of the product more accurately. Based on the results of the study it can be seen that the cost of production according to Family Furniture is Rp. 14,177,600 while according to the job order method Rp. 15,248,000. It is estimated that there is a difference of Rp. 1,070,400 with a percentage of 7%. The difference in difference is due to differences in the concept of factory overhead costs in the furniture family and according to the method of determining work costs. Family furniture calculates factory overhead costs by estimating 20% ​​of total raw material costs, direct labor costs and non-production costs.